Physiotherapy management in anal cell carcinoma following laparoscopic surgery – A Case Report (International Journal of Physiotherapy, 2024)
Background: Anorectal malignancies, wherein anal cell carcinoma comprises just 2-4% of cases, are uncommon and pose particular difficulties for treatment and recovery. Chemotherapy, radiation therapy, and surgery are a few multimodal treatments. Owing to its less invasive nature, reduced post-operative complications, reduced length of hospital stay, and faster recovery than open surgery, laparoscopic surgery, in particular has gained popularity. Physiotherapy is an essential component of this interdisciplinary approach as it offers interventions that promote physical well-being, expedite recovery, and enhance aerobic function along with muscle strength.Physiotherapists employ several strategies to encourage early movement through guided exercises and respiratory training to circumvent complications following surgery, such as deep vein thrombosis, pulmonary embolism, and muscular atrophy. Physiotherapy interventions usually start within the first 24 hours following surgery.Case Summary: This case report explains the post-operative rehabilitation of a patient who underwent laparoscopic surgery for anal cell carcinoma, wherein a structured exercise program was prescribed to the patient leading to successful recovery and return to function postoperatively.Outcome Measures: The outcome measures were the Numerical pain rating scale, Hospital anxiety and depression scale, 6-minute walk test, and Borg dyspnea scale.Conclusion: Effective physiotherapy management post-laparoscopic surgery for anal cell carcinoma involves a multifaceted approach addressing pain, mobility, pelvic floor function, respiratory health, and aerobic capacity. Tailoring physiotherapy interventions to individual patient needs and incorporating evidence-based practices are essential for optimal outcomes.